Tsar Peter (927–969) in the "Tale of the Prophet Isaiah". A few remarks - Leszka, Mirosław Jerzy (In Gremium. Studies in History, Culture and Politics, 2019)
Tale of the Prophet Isaiah is classed among the historical-apocalyptic literature. It was written at the time when the Bulgarian lands were already a part of the Byzantine Empire. In it, we find an extraordinarily interesting passage regarding Peter. The anonymous author emphasises the fact that his was a sinless life, spent in purity. Peter led a people chosen by God, similarly to a Byzantine emperor. Associating him with Constantine the Great or Constantine Porphyrogennetos makes him equal to a Byzantine ruler. This is also expressed through the statement that he was a tsar of the Bulgarians and of the Greeks. A notable feature of this portrayal of Peter in the Tale is the indication that during this ruler’s reign Bulgaria was going through a period of a particular beatitude, and abounded in all the necessary goods. Peter therefore comes across as a good, just and strong ruler.